Simulating the influence of greenhouse gases on the climate of West Africa (2019)
The response of climate to perturbations in GHGs is location dependent. Six experiments: control (CTRL); double CH4; double CO2; double N2O; halved CFC11 and halved CFC12 were carried out to reveal the local area response to different GHGs levels in the atmosphere over West Africa. Double CH4, CO2 and N2O generally induce wetness but they also induce localized dryness at the hilly and mountainous areas of SW Ghana, Central Nigeria, Northern Cameroon and South-eastern Central African Republic. Increase in ground temperature is induced by double GHGs with intensified warming at the north by double CO2. However, patches of cooling are induced at the north. Changes in specific humidity induced by double CO2, CH4 and N2O are similar. Intensified tropical easterly jet is induced by double GHGs. A dipole anomaly of wind with positive at the lower latitude and negative at higher latitude is induced at the northern part of West Africa. Significant reduction in cloud water content is induced from 900 to 400 hPa and 0 and 15oN.